Rise of the 5th estate: how online public discourse on Najib Razak’s 1MDB scandal foreshadowed Pakatan Harapan’s win in the 14th general election - Nur Haniz Mohd Nor,; Amira Sariyati Firdaus,; Surinderpal Kaur Chanan Singh, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Public discourse commonly takes place in public forums of free media. The 4th estate provides an external dimension to the democratic check and balance to the executive (1st estate), the legislative (2nd estate), and the judiciary (3rd estate). This paper discusses the rise of a social media 5th estate, as exemplified by online public discourse surrounding the 1 Malaysia Development Berhad (1MDB) scandal, and the country’s ensuing electoral change of government. Drawing upon thematic analyses of 1MDB-related comments in the official Facebook page of Free Malaysia Today, this paper illustrates the rise of a social media 5th estate in the run-up to Pakatan Harapan’s win in the Malaysian 2018 14th General Election. Since international public disclosure in 2015 of former Malaysian premier Najib Razak’s purported siphoning of billions of ringgit from 1MDB, the scandal continues to be a trending topic on Malaysian social media. The online discourse of 1MDB evolved from heated posts discussing Najib’s culpability and criticism of his Barisan Nasional administration, into support to the opposition Pakatan Harapan coalition, particularly in the run-up to the 14th Malaysian General Elections (GE14) that was held on 9th May 2018. Pakatan Harapan’s win, following the social media support, exemplifies the power of a netizen-fuelled 5th estate.